Get ready for short tandem repeats analysis using long reads-the challenges and the state of the art - Marija Chaushevska; Marija Chaushevska; Karmele Alapont-Celaya; Anne Kristine Schack; Anne Kristine Schack; Lukasz Krych; M. Carmen Garrido Navas; M. Carmen Garrido Navas; M. Carmen Garrido Navas; Anastasia Krithara; Gjorgji Madjarov; Gjorgji Madjarov (Frontiers in Genetics)
Short tandem repeats (STRs) are repetitive DNA sequences that contribute to genetic diversity and play a significant role in disease susceptibility. The human genome contains approximately 1.5 million STR loci, collectively covering around 3% of the total sequence. Certain repeat expansions can significantly impact cellular function by altering protein synthesis, impairing DNA repair, and leading to neurodegenerative and neuromuscular diseases. Traditional short-read sequencing struggles to accurately characterize STRs due to its limited read length, which limits the ability to resolve repeat expansions, increases mapping errors, and reduces sensitivity for detecting large insertions or interruptions. This review examines how long-read sequencing technologies, particularly Oxford Nanopore and PacBio, overcome these limitations by enabling direct sequencing of full STR regions with improved accuracy. We discuss challenges in sequencing, bioinformatics workflows, and the latest computational tools for STR detection. Additionally, we highlight the strengths and limitations of different methods, providing deeper insight into the future of STR genotyping.